Pelatihan Penulisan Ilmiah Berbasis AI: Meningkatkan Kompetensi Penelitian Mahasiswa Pascasarjana Universitas Pakuan - Santoso, Teguh Iman (Penerbit Widina, Widina Media Utama, 2024)
The use of Artificial Intelligence (AI) technology in the process of writing scientific articles has the potential to improve the research competence of postgraduate students, both in terms of efficiency, quality, and development of ethical perspectives. The hybrid workshop training themed